RNA regulation in brain function and disease 2022 (NeuroRNA): A conference report - Piwecka, Monika; Fiszer, Agnieszka; Rolle, Katarzyna; Olejniczak, Marta (Frontiers in Molecular Neuroscience, 2023)
Recent research integrates novel technologies and methods from the interface of RNA biology and neuroscience. This advancing integration of both fields creates new opportunities in neuroscience to deepen the understanding of gene expression programs and their regulation that underlies the cellular heterogeneity and physiology of the central nervous system. Currently, transcriptional heterogeneity can be studied in individual neural cell types in health and disease. Furthermore, there is an increasing interest in RNA technologies and their application in neurology. These aspects were discussed at an online conference that was shortly named NeuroRNA.